2009
DOI: 10.1590/s0004-282x2009000500032
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and sudden unexpected death in epilepsy?: Eat more fish! A group hypothesis

Abstract: -Epilepsy is the commonest serious neurological disorder and individuals with epilepsy are at higher risk of death than the general population and sudden unexpected death in epilepsy (SUDEP) is the most important direct epilepsy-related cause of death. Potential pathomechanisms for SUDEP are unknown, but it is very probable that cardiac arrhythmias during and between seizures play a potential role. The ultimate goal of SUDEP research is to develop methods to prevent it and nutritional aspects such as omega-3 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Deficiency of fatty acids during the pre- and early postnatal life periods has been associated with a delay in the growth and maturation of the myelin in the brain frontal lobe of offspring ( 74 ). In seizure disorder, n-3 PUFA supplementation has been found to promote neuroprotection ( 75 ). The n-3 PUFA can play a vital role in neuronal functions throughout the life via several proposed mechanisms ( 76 ) including maintaining the cell membrane liquidity ( 77 ), myelination ( 78 ), neural growth, gene expression ( 76 ), and its anti-inflammatory properties ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of fatty acids during the pre- and early postnatal life periods has been associated with a delay in the growth and maturation of the myelin in the brain frontal lobe of offspring ( 74 ). In seizure disorder, n-3 PUFA supplementation has been found to promote neuroprotection ( 75 ). The n-3 PUFA can play a vital role in neuronal functions throughout the life via several proposed mechanisms ( 76 ) including maintaining the cell membrane liquidity ( 77 ), myelination ( 78 ), neural growth, gene expression ( 76 ), and its anti-inflammatory properties ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…While a precise FA deficiency has not been linked with the development of SD, research (discussed below) has indicated omega-3 supplementation leads to a decrease in severity of symptoms and promotes neuroprotection (Cysneiros et al, 2009), thus indicating EFAs may play a role in seizure disorders (Scorza et al, 2008;Tavriger, 1966;Yuen & Sander, 2004;Yuen et al, 2005).…”
Section: Clinical Comorbiditiesmentioning
confidence: 99%
“…The investigation into the efficacy of omega-3 FA supplementation as a treatment for epilepsy has also yielded mixed results (Cysneiros, et al, 2009;Ferrari, et al, 2008;Yuen & Sander, 2004;Yuen, et al, 2005). Supplementation of a DHA/EPA mixture leads to an increase in blood concentrations of DHA and EPA, as well as reduced seizure susceptibility, however, decreased seizure frequency was only sustained for the first half of a twelve week study by Yuen et al (2005).…”
Section: Omega-3 Supplementation 10mentioning
confidence: 99%
See 1 more Smart Citation